Program Evaluation: exploring health disparities that impact chronic pain referrals within a VA Health Care System - Hanson, Eric R.; Quist, Heidi E.; Mintert, Jeffrey S.; Arshad, Mahreen; Friedman, Brittany L.; Pleasant, Alexandra; Monico-Cristales, N. Stacey; Tillman, Rhonda; Mehelis, Mark; Karnik, Anita; Sonder, Anais; Mardian, Aram S. (Frontiers in Pain Research, 2023)
The present program evaluation study examines sociodemographic characteristics of Veterans in the Phoenix VA Health Care System who have back pain, and specifically the likelihood of those characteristics being associated with a referral to the Chronic Pain Wellness Center (CPWC) in the year 2021. We examined the following characteristics: Race/ethnicity, gender, age, mental health diagnosis, substance use disorder diagnosis, and service-connected diagnosis. Our study used cross sectional data from the Corporate Data Warehouse for 2021. 13624 records had complete data for the variables of interest. Univariate and multivariate logistic regression was used to determine the likelihood of patients’ being referred to the Chronic Pain Wellness Center. The multivariate model found under-referral to be significant for younger adults and for patients who identified as Hispanic/Latinx, Black/African American, or Native American/Alaskan. Those with depressive disorders and opioid use disorders, on the other hand, were found to be more likely to be referred to the pain clinic. Other sociodemographic characteristics were not found to be significant. Study limitations include the use of cross-sectional data, which cannot determine causality, and the inclusion of patients only if the ICD-10 codes of interest were recorded for an encounter in 2021 (i.e., a prior history of a particular diagnosis was not captured). In future efforts, we plan to examine, implement, and track the impact of interventions designed to mitigate these identified disparities in access to chronic pain specialty care.